2020
DOI: 10.1007/s11695-020-04686-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss After Bariatric Surgery Significantly Improves Carotid and Cardiac Function in Apparently Healthy People with Morbid Obesity

Abstract: Purpose Obesity clearly increases cardiovascular risk, often inducing high blood pressure (BP), impaired left ventricular (LV) function, and increased arterial stiffness. Intensive weight loss and bariatric surgery induce improvement in hypertension and diabetes for morbid obesity. Carotid artery haemodynamics is a powerful prognostic indicator for stroke and cognitive decline independent of BP. The aim of this study was to evaluate the impact of a 3-stage bariatric strategy of diet, bariatric surgery, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…), following an earlier reported protocol (Giannattasio et al, 2008 ). Simultaneous ultrasound acquisition of D and U was performed on the right CCA using a 10.0‐MHz linear array probe with radiofrequency data output at the frequency of 1 kHz connected to an Aloka Alpha10 Prosound system (Hitachi Ltd., Tokyo, Japan) as reported previously (Giudici et al, 2020 ). Given the impossibility of placing a pressure tonometer on the right CCA due to the presence of the ultrasound probe, P was acquired at the left CCA using a PulsePen (DiaTecne, Milan, Italy) with sampling frequency 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…), following an earlier reported protocol (Giannattasio et al, 2008 ). Simultaneous ultrasound acquisition of D and U was performed on the right CCA using a 10.0‐MHz linear array probe with radiofrequency data output at the frequency of 1 kHz connected to an Aloka Alpha10 Prosound system (Hitachi Ltd., Tokyo, Japan) as reported previously (Giudici et al, 2020 ). Given the impossibility of placing a pressure tonometer on the right CCA due to the presence of the ultrasound probe, P was acquired at the left CCA using a PulsePen (DiaTecne, Milan, Italy) with sampling frequency 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Thus arterial stiffness may be evaluated through comprehensive assessment of arterial distensibility in the clinical setting to pinpoint vascular health and predict future cardiovascular risk. Many, although not all, studies have found that weight loss reduces arterial stiffness, indicating the reversible nature of obesity-induced vascular stiffness ( 212 , 215 , 216 ). A better understanding of arterial stiffness in overweight and obesity should assist therapeutic strategies to reduce obesity-associated inordinate CVD risks.…”
Section: Cardiac Remodeling In Obesitymentioning
confidence: 99%
“…Even in a very recent study on this issue [ 12 ], no significant decrease in AS was observed 1-month post-BS except in patients with preoperative pathologic PWV. And another group reported very recently significant changes in PWV at 8 months after BS [ 27 ]. Along these lines, the second important point is that we have demonstrated that main changes in the different markers of AS occur in patients with lowest PWV, suggesting that perhaps PWV is a stronger marker of organ damage than AIx@75 or PP, and thus less susceptible to modification even after losing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have previously suggested that the RAAS is an important determinant of AS, in addition to BP and other factors. Multiple mechanisms are responsible for the RAAS activation in obesity, including adipose tissue-derived RAAS components that might be involved in regulation of BP and AS through local production of angiotensin (Ang) II and aldosterone, conversion of adipocyte-derived angiotensinogen by systemic renin and ACE-activity, or forming Ang via alternative routes due to the presence of cathepsins and chymase in human adipose tissue [ 27 , 30 ]. The main changes in this BARIHTA study were observed in ACE and ACE2, but no significant change was found in PRA or plasma aldosterone concentration 1-month post-BS, nor were there any correlations between their changes and improvement on any AS marker.…”
Section: Discussionmentioning
confidence: 99%